Ultrasound-Mediated Drug Delivery in Cancer Therapy: A Review - AlSawaftah, Nour Majdi (2020)
The use of ultrasound as a medical diagnostic tool began in the 1940s. Ever since, the medical applications of ultrasound have included imaging, tumor ablation, and lithotripsy; however, an ever-increasing body of literature demonstrates that ultrasound has potential in other medical applications, including targeted drug delivery. Site-specific drug delivery involves delivering drugs to diseased areas with a high degree of precision, which is particularly advantageous in cancer treatment as it would minimize the adverse side effects experienced by patients. This review addresses the ability of ultrasound to induce localized and controlled drug release from nanocarriers, namely micelles and liposomes, utilizing thermal and/or mechanical effects. The interactions of ultrasound with micelles and liposomes, the effects of the lipid composition, and ultrasound parameters on the release of encapsulated drugs are discussed. In addition, a survey of the literature detailing some in vitro and in vivo ultrasound triggered drug delivery systems is presented.